2022
DOI: 10.1186/s12920-022-01402-w
|View full text |Cite
|
Sign up to set email alerts
|

The relationships of OSBPL3 expression with KI-67 expression and KRAS mutations in CRC: implications for diagnosis and prognosis

Abstract: Background OSBPL3 is overexpressed in a variety of malignancies and is closely associated with tumor growth and metastasis. However, its expression and function in colorectal cancer (CRC) are unclear. We aimed to investigate its prognostic and therapeutic value in this disease by detecting its expression in CRC and its correlation with the clinicopathological characteristics and prognosis of patients. Methods A total of 92 CRC samples were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…Meanwhiles, our study revealed that OSBPL3 were associated with the T and N stage of CRC, it's similar to Hao's study. Furthermore, Zhang's research suggests that CRC samples with high OSBPL3 expression exhibit more KRAS mutations, which is consistent with our findings [ 31 ]. However, these results indicated the expression of OSBPL3 had changed in CRC.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhiles, our study revealed that OSBPL3 were associated with the T and N stage of CRC, it's similar to Hao's study. Furthermore, Zhang's research suggests that CRC samples with high OSBPL3 expression exhibit more KRAS mutations, which is consistent with our findings [ 31 ]. However, these results indicated the expression of OSBPL3 had changed in CRC.…”
Section: Discussionsupporting
confidence: 92%
“…The most frequent mutation among our patients was c.35G>T p.Gly12Val (32.56%), followed by c.35G>A p.Gly12Asp (20.93%). These two KRAS mutations in codon 12, as well as the codon 13 c.38G>A (p.Gly13Asp) mutation, are the most common mutations among the European population as G12D and G12V are vying for the top spot [ 28 , 29 , 30 , 31 ]. The poor prognosis associated with exon 2 KRAS mutations is well documented, but the prognostic or predictive value of mutations in codons 12 and 13 remains a subject of debate.…”
Section: Discussionmentioning
confidence: 99%
“…17 Previous studies showed that Ki67 is a prognostic marker in many tumors, such as colorectal cancer, breast cancer, lymphoma, prostate cancer, and laryngeal cancer. [18][19][20][21][22] Additionally, the Ki67 labeling index (LI) of SGC (46.1% ± 3.0%) was higher than that of normal conjunctiva (6.8% ± 32.3%). 23 Similarly, high Ki67 expression was associated with poor outcomes in eyelid SGC recurrence and lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Ki67 is a potent marker for cellular proliferation, and its primary function involves acting as a biosurfactant that promotes the dispersion of chromosomes during mitosis 17 . Previous studies showed that Ki67 is a prognostic marker in many tumors, such as colorectal cancer, breast cancer, lymphoma, prostate cancer, and laryngeal cancer 18–22 . Additionally, the Ki67 labeling index (LI) of SGC (46.1% ± 3.0%) was higher than that of normal conjunctiva (6.8% ± 32.3%) 23 .…”
Section: Discussionmentioning
confidence: 99%